2020
DOI: 10.1021/acs.biomac.0c00210
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Initiated Controlled Radical Polymerization Approach to In Situ Cross-Link Cellulose Nanofibrils with Inorganic Nanoparticles

Abstract: This paper investigates a strategy to convert hydrophilic cellulose nanofibrils (CNF) into a hydrophobic highly cross-linked network made of cellulose nanofibrils and inorganic nanoparticles. First, the cellulose nanofibrils were chemically modified through an esterification reaction to produce a nanocellulose-based macroinitiator. Barium titanate (BaTiO3, BTO) nanoparticles were surface-modified by introducing a specific monomer on their outer-shell surface. Finally, we studied the ability of the nanocellulos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 64 publications
1
33
0
Order By: Relevance
“…However, the authors reported that cellulose aerogels exhibited excellent antibacterial activity with the amoxicillin dose-dependent activity 67 . Immobilization of certain doses of antibiotic inside the aerogel network enhances the activity of the antibiotic, which has been demonstrated in a previous study 68 .…”
Section: Antibacterial Applications Of Cellulose-based Aerogelssupporting
confidence: 70%
See 1 more Smart Citation
“…However, the authors reported that cellulose aerogels exhibited excellent antibacterial activity with the amoxicillin dose-dependent activity 67 . Immobilization of certain doses of antibiotic inside the aerogel network enhances the activity of the antibiotic, which has been demonstrated in a previous study 68 .…”
Section: Antibacterial Applications Of Cellulose-based Aerogelssupporting
confidence: 70%
“…Cellulose has a unique surface chemistry, permitting it to cross-link with many materials, including protein extracts, antibiotics, and even metal nanoparticles 68 . Zuguang et al 69 prepared hybrid cellulosebased aerogels using silver nanoparticles as antibacterial materials.…”
Section: Antibacterial Applications Of Cellulose-based Aerogelsmentioning
confidence: 99%
“…[ 17 ] Through similar reactions, methacrylate groups have been bonded to cellulose derivatives. [ 18,19 ] These completely aqueous modifications can be carried out without the solvent exchanges needed to create CNF macroinitiators, [ 9,20 ] although the efficiency of the functionalization will decrease because of the competing hydrolysis reaction. This functionalization enables a third method to graft polymers to surfaces where a polymerizing chain reacts with a monomer tethered to a surface and continues to polymerize on, following a “grafting‐through” process.…”
Section: Methodsmentioning
confidence: 99%
“…The loaded aerogels exhibited excellent antibacterial activity with prolonged release of the antibiotic. The ability of cellulose to cross-link with other materials and make many surface interactions with polar and even non-polar compounds enhanced its potential for different biomedical applications [ 118 ]. A novel hybrid aerogel was fabricated by Zuguang et al [ 119 ].…”
Section: Biopolymer-based Aerogels For Antibacterial Deliverymentioning
confidence: 99%